Gestión de riesgos laborales en los trabajadores de Carrocerías Yaulema Jr en el período 2024 - Correa Cruz, Guissepe Alvaro (2025)
This study analyzed occupational risks in the bodywork sector and proposed preventive measures to mitigate them. The objective was to manage occupational risks in the workers of Carrocerías Yaulema Jr. in the period 2024, through an explanatory and descriptive approach with a mixed design. On the other hand, in the identification stage, the direct observation technique was applied together with the help of the hazard identification matrices; in addition, surveys were developed according to the level of predominance, such as physical risks; ergonomic risks and chemical risks. Subsequently, the measurement was carried out using methods based on international standards for physical risks; for ergonomic risks, the RULA and NIOSH methods were applied; for psychosocial risks, the questionnaire issued by the Ministry of Labor was applied. Once the risks were identified, they were evaluated using the INSST NTP 330 methodology. Based on the results obtained, preventive management was proposed with traditional controls at the source, the environment, and the worker, as established in the NTP 330 matrix, as well as intervention measures in accordance with ISO 45001. In addition, the company was provided with a model for preparing a prevention plan to reduce exposure to hazards and improve occupational safety performance; these actions not only contribute to personnel protection, but also optimize production processes by reducing the incidence of occupational accidents and illnesses.